ANALISIS DAN PEMETAAN STRATEGI PT INDOFOOD MENGGUNAKAN METODE BSC DAN MC FARLAN - Melenia Yolanda Fitri; Dinda Dwi Anita Ningrum; Lailatus Safitri Afifaini (JURNAL TEKNOLOGIA, 2021)
Technology is now the reason for companies to develop and compete on the international scene. Performance assessment is one of the main factors in developing a company. To know the performance of PT. Indofood, especially in the production of instant noodles, it is necessary to measure the achievement of the strategies. IT/IS strategy planning consists of the preparation of Environmental Condition Analysis (AKL) both internal and external companies, Balance Scorecard (BSC), Cascading Program, Pick Chart to the completion of Portfolio Mc Farlan. This stage is the flow of the creation of new strategies and mapping the level of interest in the implementation of IT / IS in the company.